CP violation of the loop induced H± → W±Z decays in the general two Higgs doublet model* - Mura Yushi; Kanemura Shinya (EPJ Web of Conferences)
New sources of CP violation are necessary to solve the problem of the baryon asymmetry of the Universe. Extending the Higgs sector is one way to introduce such new CP violating phases, and studying observables resulting from the CP violation is important to test the model in future experiments. In these proceedings, we discuss the loop induced H±W±Z vertices in the CP violating general two Higgs doublet model, summarizing our results [1]. We evaluate impacts of the CP violation on the decays H± → W±Z through these vertices, and find that the difference between the decays H+ → W+Z and H− → W−Z is sensitive to the CP violating phases in the model.